RAND DESIGN GENERASI EMAS 2045: TANTANGAN DAN PROSPEK PENDIDIKAN KEWARGANEGARAAN UNTUK KEMAJUAN INDONESIA - Sabit Irfani; Dwi Riyanti; Ricky Santoso Muharam; Suharno (Balitbang Kemendikbud, 2021)
This study aims to analyze the challenges of citizenship issues in preparing Indonesia's golden generation in 2045. This research is content analysis research with a qualitative approach. Data were collected through observation and tracing documents and archives. The results show great challenges of Indonesian as a state in terms of maintaining the foundational philosophical theory of Pancasila. This determines the importance of a study of civic education as the spearhead in preparing the generation that will inherit the nation and state of Indonesia. In 2045, Indonesia expects to have a golden generation. This of course requires Indonesian as a state to prepare its human resources, namely the younger generation, to face this momentum well. The golden generation of Indonesia is expected to be a generation that is tough, thinks forward, and always upholds the values of Pancasila. The golden generation of Indonesia in 2045 is the hope for the future of the nation. Civics as a subject in school has a paramount role in preparing Indonesia’s golden generation in 2045. Civics must be able to solve challenges such as intolerance, the ideology of other nations, and globalization. The prospect of civic education is being promoted as a panacea for solving problems that exist in Indonesia as a nation.